Study on the impact of the euro on trade and foreign direct investment - Baldwin, Richard E.; DiNino, Virginia; Fontagne, Lionel; De Santis, Roberto A.; Taglioni, Daria; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission : Directorate-General for Economic and Financial Affairs, 2008)
The introduction of the euro was the world's largest economic 'experiment.' This experiment opens the door to a major advance in our understanding of how a common currency affects economic activity. When it comes to the euro's trade effects the first contribution of this report is to refine "the number". Using the latest data and best empirical methodology, we confirm the received wisdom that the euro has promoted trade significantly, with the aggregate impact being in the range of 5% or so. The second main contribution of this report was to advance and refine our understanding of exact how the euro was boosting trade. The euro boosted trade inside the Eurozone since it lowered the relative price of traded goods coming from the Eurozone. The second main channel is the newly-trade goods channel. The third main contribution of the report concerns the euro's pro-FDI effects.
Economic Papers.